Pengembangan Kurikulum PAI dalam Meningkatkan Mutu Pendidikan - Rani Nurfitri; Amelia Amelia; Mustafiyanti Mustafiyanti (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
In education, of course there is something called a curriculum, the curriculum needs to be developed so that it can help improve the quality of education which will be very beneficial for school principals, teachers, staff and student. The curriculum is a dynamic teaching and learning vehicle so it needs to be developed and assessed continuously in accordance with existing developments in society. Curriculum development is a process that determines how the curriculum will run.